Ultrafast and highly efficient Cd(II) and Pb(II) removal by magnetic adsorbents derived from gypsum and corncob: Performances and mechanisms - Yuhong Yang; Tongtong Han; Jing Wang (Ecotoxicology and Environmental Safety, 2024)
The utilization of gypsum and biomass in environmental remediation has become a novel approach to promote waste recycling. Generally, raw waste materials exhibit limited adsorption capacity for heavy metal ions (HMIs) and often result in poor solid–liquid separation. In this study, through co-pyrolysis with corncob waste, titanium gypsum (TiG) was transformed into magnetic adsorbents (GCx, where x denotes the proportion of corncob in the gypsum–corncob mixture) for the removal of Cd(II) and Pb(II). GC10, the optimal adsorbent, which was composed primarily of anhydrite, calcium sulfide, and magnetic Fe3O4, exhibited significantly faster adsorption kinetics (rate constant k1 was 218 times and 9 times of raw TiG for Cd(II) and Pb(II)) and higher adsorption capacity (Qe exceeded 200 mg/g for Cd(II) and 400 mg/g for Pb(II)) than raw TiG and previous adsorbents. Cd(II) removal was more profoundly inhibited in a Cd(II) + Pb(II) binary system, suggesting that GC10 showed better selectivity for Pb(II). Moreover, GC10 could be easily separated from purified water for further recovery, due to its high saturation magnetization value (6.3 emu/g). The superior removal capabilities of GC10 were due to adsorption and surface precipitation of metal sulfides and metal sulfates on the adsorbent surface. Overall, these waste-derived magnetic adsorbents provide a novel and sustainable approach to waste recycling and the deep purification of multiple HMIs.